Digital health promotion, prevention and health literacy measures among seafarers and crews on cargo and passenger ships: A scoping review - Chiara Reck; Lukas Belz; Dorothee Dengler; Nora Maria Puls; Volker Harth; Marcus Oldenburg (PLOS One, 2026)
Introduction The unique occupational conditions of seafaring are associated with increased physical and psychological stress and significantly complicate common approaches to health promotion and prevention. Digital health technologies are therefore considered promising alternatives that can better address barriers to access, infrastructural shortcomings and cultural diversity. Objective The aim is to provide a comprehensive overview of scientific evidence about digital measures used for health promotion and prevention among seafarers and crew members on merchant ships (cargo/passenger). As secondary study aim, digital practical programs established to promote health at sea will also be presented. Methods This scoping review was conducted in accordance with the updated methodological guidelines from the Joanna Briggs Institute (JBI) and the PRISMA-ScR checklist. The protocol was prospectively registered in the Open Science Framework (OSF). The literature search was conducted systematically in Scopus, Web of Science, PubMed, and LIVIVO, and study selection was carried out based on the selection criteria. In addition, a targeted web search for digital practical programs was conducted. Results A total of 1,711 sources were identified, 68 full-text articles were screened, and 9 studies were included in the qualitative analysis. The evidence base is highly heterogeneous, consisting of various study designs ranging from pilot studies to one randomized controlled trial (RCT). Only articles on digital health promotion and prevention were identified. No studies were found that examined digital health literacy. All included studies focused exclusively on seafarers working on cargo ships. Four studies investigated behavioral approaches, while two studies focused on structural approaches and the remaining three studies dealt with blended concepts. Thematic focus varies, addressing topics such as nutrition, mental health, skin cancer prevention, and digital prediction models. In addition, six digital practical programs on topics such as physical activity, mental health, sleep and stress management, and nutrition were identified. Conclusions An overview of the current state of research and practical applications regarding digital health promotion and prevention among seafarers on merchant ships was provided. The topic has been scarcely addressed in the shipping industry to date. Concurrently, the heterogeneity of the evidence, the restricted number of relevant studies, and the variable quality of the studies indicate a necessity for further research. Academic research should also address the topic of digital health literacy and the demands of crew members on passenger ships. Based on the findings, it is recommended that shipping companies take responsibility for promoting the health of seafarers on board their ships by empowering their crews.